The Moderating Role of Emotional Intelligence in the Influence of Work Culture on the Commitment and Performance of Health Workers - Solichin, Much. Riyadus; Parmin (Jurnal Economic Resource, 2025)
This study aims to examine the moderating role of emotional intelligence in the relationship between work culture, commitment, and performance of healthcare workers at Muhammadiyah Amanah Sumpyuh Hospital, Banyumas. This study used a quantitative approach and involved 75 healthcare workers. Data were collected through a standardized questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that work culture significantly influenced commitment and performance, while commitment did not directly influence performance. Emotional intelligence was shown to act as a moderating variable that strengthened the relationship between work culture and commitment and performance. These findings suggest that strengthening work culture supported by the development of emotional intelligence can improve the effectiveness of hospital organizations. This study provides theoretical and practical contributions to human resource management in the healthcare sector, particularly in the context of religious-based hospitals.